Services – SERVICES 2018 : 14th World Congress, held as part of the Services Conference Federation, SCF 2018, Seattle, WA, USA, June 25-30, 2018, Proceedings /: 14th World Congress, held as part of the Services Conference Federation, SCF 2018, Seattle, WA, USA, June 25-30, 2018, Proceedings. (2018) - Unknown
No abstract available